Stability Analysis of SARS-CoV-2 with Heart Attack Effected Patients and Bifurcation - Ahmad, Aqeel; Abbas, Safdar; İnç, Mustafa; Ghaffar, Abdul (Wiley-V C H Verlag Gmbh, 2024)
The aim of this study is to analyze and investigate the SARS-CoV-2 (SC-2) transmission with effect of heart attack in United Kingdom with advanced mathematical tools. Mathematical model is converted into fractional order with the help of fractal fractional operator (FFO). The proposed fractional order system is investigated qualitatively as well as quantitatively to identify its stable position. Local stability of the SC-2 system is verified and test the proposed system with flip bifurcation. Also system is investigated for global stability using Lyponove first and second derivative functions. The existence, boundedness, and positivity of the SC-2 is checked which are the key properties for such of type of epidemic problem to identify reliable findings. Effect of global derivative is demonstrated to verify its rate of effects of heart attack in united kingdom. Solutions for fractional order system are derived with the help of advanced tool FFO for different fractional values to verify the combine effect of COVID-19 and heart patients. Simulation are carried out to see symptomatic as well as a symptomatic effects of SC-2 in the United Kingdom as well as its global effects, also show the actual behavior of SC-2 which will be helpful to understand the outbreak of SC-2 for heart attack patients and to see its real behavior globally as well as helpful for future prediction and control strategies. The authors considered the fractional order SC-2 model, which shows the history of heart attack patients using the fractal fractional operator. They have offered some recommendations for containing this virus so that the community can overcome this situation. They presented analyzes to see how much the dangerous coronavirus and the deadly SC-2 disease epidemic affected the heart. image
Keywords: boundedness; flip bifurcation; fractal fractional; stability analysis